Combined microbiome and metabolome analysis of gut microbiota and metabolite interactions in chronic spontaneous urticaria - Luo, Zhen; Jin, Zhangsi; Tao, Xiaoran; Wang, Ting; Wei, Panling; Zhu, Caihong; Wang, Zaixing (Frontiers in Cellular and Infection Microbiology, 2023)
Background: The pathogenesis of chronic spontaneous urticaria (CSU) is unclear, and it turned out to be involved in biological processes, such as autoimmunity, autoallergy, inflammation, and coagulation. The gut microbiota plays an important role in immune and inflammatory diseases. However, the relationship between chronic spontaneous urticaria and the gut microbiota remains unknown. Methods: The stool and serum samples were taken from 15 CSU patients and 15 normal controls. Changes in the composition of gut microbiota and serum metabolism in CSU patients and normal controls were analyzed by 16S ribosomal RNA (rRNA) gene sequencing and untargeted metabolomics. Results: The results of 16S rRNA gene sequencing showed that compared with normal controls, CSU patients had increased α-diversity of gut microbiota and significant differences in β-diversity. At the phylum level, the relative abundance of Firmicutes increased and the relative abundance of Bacteroidetes and Proteobacteria decreased in CSU patients compared with healthy controls. At the genus level, six kinds of bacteria were significantly enriched in CSU patients and five in normal controls. Metabolomic analysis revealed altered levels of metabolites such as unsaturated fatty acids and purines. Correlation analysis of gut microbiota and metabolites showed that Lachnospira was negatively correlated with arachidonic acid, and Gemmiger was also negatively correlated with (±)8-HETE. Conclusion: This study suggests that changes in gut microbiota and metabolites may play a role in immune and inflammatory pathways in the pathogenesis of CSU patients.